2011
DOI: 10.1007/s10620-011-1893-6
|View full text |Cite
|
Sign up to set email alerts
|

The −409 C/T Genotype of PRSS1 Protects Against Pancreatic Cancer in the Han Chinese Population

Abstract: The -409 C/T genotype of PRSS1 was revealed to be a protective factor against pancreatic cancer in the Han Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In a recent genomewide association study, variant c.-408CϾT (i.e., the T allele) was demonstrated to have a small protective effect against chronic pancreatitis presumably by lowering trypsinogen expression (64). The C allele of the same variation (erroneously reported as Ϫ409C/T) was previously claimed to offer protection against pancreatic cancer in a Chinese population; however, independent confirmation is lacking (31).…”
Section: Common Polymorphisms In Prss1mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent genomewide association study, variant c.-408CϾT (i.e., the T allele) was demonstrated to have a small protective effect against chronic pancreatitis presumably by lowering trypsinogen expression (64). The C allele of the same variation (erroneously reported as Ϫ409C/T) was previously claimed to offer protection against pancreatic cancer in a Chinese population; however, independent confirmation is lacking (31).…”
Section: Common Polymorphisms In Prss1mentioning
confidence: 99%
“…Two studies described PRSS1 variants in Chinese patients with pancreatic cancer (p.T135A, p.T137M, c.454ϩ36TϾC, and c.454ϩ157CϾG in intron 3), which are in all likelihood incidental findings unrelated to pathology (13,68). The same group proposed a strong protective effect for the C allele of the common polymorphic variant c.Ϫ408CϾT (erroneously reported as Ϫ409C/T) against pancreatic cancer (31). Variant p.L104V was reported in two female members of a Chinese family with familial solid pseudopapillary tumor of the pancreas and in two healthy male relatives (17).…”
Section: Prss1 Variants In Conditions Unrelated To Pancreatitismentioning
confidence: 99%
“…Binding to the AP-1 site of PCNA gene, AP-1 regulates the mRNA of PCNA gene on the transcription affected the synthesis of PCNA protein, and then induces carcinogenesis. Corresponding research results were published in Digestive Diseases & Science and Chinese Medical Journal [30,31]. Meanwhile, it also has been confirmed that the theory of AAT compensatory increase is to neutralize and inhibit the activation of trypsin and other proteolytic enzymes so to inhibit the proliferation and spread of tumor cells [23][24][25][26][27].…”
Section: New Interpretation Of Enzymes and Anti-enzyme Imbalance Causmentioning
confidence: 71%
“…The high mortality rate of pancreatic cancer has become the bottleneck to further improving the long-term efficacy, and it is urgent to find novel means to predict pancreatic cancer. [2,3] A DNA electrochemical biosensor can convert the presence of target DNA into an electrical signal and carries the advantages of being rapid, sensitive, and easy to operate and having pollution-free characteristics. It takes in an important role in molecular recognition, separation, and purification of genes and it has become a frontier topic in clinical diagnostic testing and genetic diseases and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[10] What is more, it has been known that mutations or polymorphisms of PRSS1 gene serve as molecular markers of pancreatic cancer. [2,3] We will build enzyme-based biosensor technology to detect PRSS1 genotype. A schematic diagram of the biosensor is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%